Modified Failure Criterion to Predict Ultimate Strength of Circular Columns Confined by Different Materials - Girgin, Z. Canan (AMER CONCRETE INST, 2009)
This study addresses the extension of a failure criterion developed for rock data to small or near full-size circular concrete columns confined by different materials. Initially, a wide range database on small-scale specimens confined by fiber-reinforced polymer (FRP) sheets or tubes and analytical studies were evaluated to predict the ultimate compressive strength. Then, the reinforced concrete (RC) short-columns retrofitted with FRP jacket were examined through available data. The research further covers middle- or near full-scale columns confined by FRP composites and steel reinforcement. All of these estimations were conducted within a unified approach to the failure criterion. Thus, the ultimate compressive strength for different confining materials can be predicted easily and systematically.
Keywords: confinement; fiber-reinforced polymers; reinforced concrete; sheet; strength; tube; REINFORCED-CONCRETE COLUMNS; COMPOSITE JACKETED CONCRETE; STRESS-STRAIN MODEL; COMPRESSIVE BEHAVIOR; TRIAXIAL COMPRESSION; DESIGN EQUATIONS; TENSILE-STRENGTH; FIBER COMPOSITES; FRP; DUCTILITY; Construction & Building Technology; Engineering; Materials Science